A-134 A Comparison Between English-Speaking and Mandarin-Speaking Adolescent Student Athletes on Baseline Preseason ImPACT® Neurocognitive Performances and Symptom Reporting. (28th August 2020) - G, Iverson; J, Karr; Y, Hong; C, Yang; B, Maxwell; P, Berkner
Abstract: Objective: Student athletes commonly complete baseline preseason assessments of neurocognitive performances and symptom reporting using ImPACT®. Some past researchers have examined differences in performances and symptoms based on language of administration and racial/ethnic identity. This study examines differences between Mandarin-speaking and English-speaking student athletes on ImPACT® at preseason assessments. Method: Participants included 252 adolescent student athletes who completed preseason baseline ImPACT® testing in Mandarin and 252 participants who completed testing in English, matched on age, gender, and health and academic history. These groups were compared on neurocognitive composite scores and symptom ratings. Results: Mandarin-speaking athletes performed modestly better on one of five neurocognitive composite scores (Visual Motor Speed, p < .001, d = .37). Language groups did not differ in total symptom severity, but Mandarin-speaking boys endorsed multiple physical symptoms at higher rates than English-speaking boys. Conclusions: These results suggest that the current ImPACT® neurocognitive normative data are reasonably appropriate for use with Mandarin-speaking adolescents. When back translated, a few Mandarin-language symptoms were not semantically equivalent to their corresponding English-language symptoms, but no group differences were observed for these symptoms. Modest language group differences were observed in physical symptom reporting, more so in boys than girls. Individuals of Asian descent are more likely to express their mental health concerns in somatic terms, and greater physical symptoms in Mandarin-speaking boys could correspond to an expression of psychological distress. Clinicians should be mindful of psychological functioning at baseline testing and post-concussion evaluations because students who do not identify with the dominant culture of their sporting environment might experience acculturative stress.